2017
DOI: 10.3390/ijms18081644
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Galectin-9 as a DAMP during Dengue Virus Infection in THP-1 Cells

Abstract: Damage-associated molecular patterns (DAMPs) are endogenous cellular molecules released to the extracellular environment in response to stress conditions such as virus infection. Galectins are β-galactoside-binding proteins that are widely expressed in cells and tissues of the immune system, are localized in the cell cytoplasm, and have roles in inflammatory responses and immune responses against infection. Elevated levels of galectin-9 (Gal-9) in natural human infections have been documented in numerous repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Importantly, CD11b (in the Mac-1 complex) and ICAM-1 or well-known interaction partners and Gal-9 may therefore stimulate granulocyte recruitment and infiltration to the lung [61]. When this process of Gal-9 secretion and granulocyte recruitment is continued in the lung, this results in the perpetuation of granulocyte-driven inflammation whereby Gal-9 functions as an ‘alarmin’ [23,24,62]. In line with this theory, Gal-9 −/− mice have reduced infiltration of CD11b + granulocytes upon lung infection [24].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CD11b (in the Mac-1 complex) and ICAM-1 or well-known interaction partners and Gal-9 may therefore stimulate granulocyte recruitment and infiltration to the lung [61]. When this process of Gal-9 secretion and granulocyte recruitment is continued in the lung, this results in the perpetuation of granulocyte-driven inflammation whereby Gal-9 functions as an ‘alarmin’ [23,24,62]. In line with this theory, Gal-9 −/− mice have reduced infiltration of CD11b + granulocytes upon lung infection [24].…”
Section: Discussionmentioning
confidence: 99%
“…Besides IL-6, damage-associated molecular patterns released from infected host cells cause the phenotype reprogramming of M1-like macrophages toward the M2-like phenotype. In addition to inducing the secretion of pro-inflammatory cytokines by M1-like macrophages and other APCs ( Tsai et al, 2014 ; Dapat et al, 2017 ), damage-associated molecular patternss also promote the secretion of IL-4 and IL-13, inducing the M2-like phenotype with wound healing, pro-angiogenic, and pro-fibrotic functions ( Wynn et al, 2013 ).
FIGURE 2 Targeting the SARS-CoV-2 infection process.
…”
Section: The Role Of Macrophage Phenotypes During Viral Infectionsmentioning
confidence: 99%
“…A number of viral infections are associated with an increase in galectin levels in serum and plasma, reviewed by Merani et al [106]. A recent study showed that secretion of galectin-9 increases upon dengue viral infection in human THP-1 cells, suggested to function as a protective mechanism for cells by limiting viral attachment to surface glycans [107].…”
Section: Galectinsmentioning
confidence: 99%